Solar‐to‐Hydrogen Efficiency of 9.5 % by using a Thin‐Layer Platinum Catalyst and Commercial Amorphous Silicon Solar Cells. Issue 9 (18th April 2016) - Ma, Qiang; Li, Man; Pang, Liuqing; Ren, Xianpei; Li, Can; Xu, Xixiang; Liu, Shengzhong (Frank)
Abstract: A photoelectrochemical system was set up with commercial triple‐junction solar cells to split water into hydrogen. To minimize the Pt loading and material cost and to maintain a high catalytic activity, a thin Pt layer on a high‐surface‐area Ni foam was used to catalyze the hydrogen evolution reaction. The solar‐to‐hydrogen efficiency measured from the hydrogen gas evolved is as high as 9.5 %. Abstract : I've seen the light : Commercial triple‐junction solar cells are used in a photoelectrochemical system to split water into hydrogen, and a thin Pt layer on a high‐surface‐area Ni foam is used as the hydrogen evolution reaction catalyst. The solar‐to‐hydrogen efficiency is as high as 9.5 %, which demonstrates that the thin Pt layer is effective for hydrogen generation.